O Alívio das Consciências na Certeza da Salvação: Uma pesquisa sobre a Dimensão Poimênica de "Da Vontade Cativa" (1ª parte) - Marlo Margarida, Daniel (Vox Scripturae - Revista Teológica Internacional, 2011)
This research is about the poimenical and existential aspects of the written protestant classic “The Captive Will”. It formulates relevant personal questions that are generated by reading such work, also leading itself to answer them. The research points out the historical context of the development of this work through a brief biographical aspects analysis about Martinho Lutero and Erasmo de Rotterdam, as well as through observing the questions involved in the controversy itself. It offers a summary of the theology of Lutero as the posterior and previous period to the publication of the studied work through a simple exposition of four other works written by the same author. They are carefully tied to the elaboration of a synthesis of the whole content of “The Captive Will”, exposing it on an organized and according way to the internal dynamics of its central affirmations. It explains on an understandable way the terminologies used in the theological discussion, establishing a dialogue with the certainties of Erasmo at specific opposing aspects. It investigates textual proofs that demonstrate the presence of the poimenical horizon throughout the Biblical-theological argument. It is concluded by answering the initial questions through a poimenical interpretation based on presuppositions and declarations from the studied work, proposing a change of paradigm when reading it, on a way that it becomes relevant for the life of the Christian.